HIV pre-exposure prophylaxis: scaling up for impact now and in the future - Bavinton, Benjamin R; Grulich, Andrew E (The Lancet. Public health, 2021)
More than a decade after the first efficacy evidence for oral HIV pre-exposure prophylaxis (PrEP) was reported, PrEP uptake globally has been inadequate and global HIV prevention targets have been missed. Access to PrEP is still highly concentrated in a fairly small number of countries and, even within countries with widespread PrEP access, inequalities have emerged. More ambitious, high-priority global targets for PrEP uptake are required and could accelerate the HIV prevention response in a similar way to the success of the 90-90-90 testing and treatment targets. Health systems must be PrEP-friendly and allow PrEP to be prescribed in settings already attended by large numbers of HIV-negative individuals who are at risk. Several models have been advanced for the greater demedicalisation of PrEP. Individual-level barriers to PrEP uptake and persistence have been characterised, such as low awareness, low willingness to use PrEP, and the gap between self-perceived and actual HIV risk. Overcoming these barriers will require further efforts to understand and address them first. New PrEP modalities are emerging; as more options become available, we need to develop a greater understanding of the long-term patterns of PrEP use in different populations and to develop models of such use that can accommodate people alternating through periods of use and non-use, as well as switching between dosing regimens or modalities as they become available. Scaling up PrEP is crucial to achieving the UNAIDS prevention targets for 2030. Simply getting more people onto PrEP cannot be the only goal: the big-picture definition of success for PrEP programmes must be their impact on the HIV epidemic.